Novedades en el género Ceroxylon (Palmae) - Galeano Gloria (Caldasia, 1995)
Four new species and one subspecies of the genus Ceroxylonare described and illustrated; they are: C. amazonicum, C. echinulatum, and C. alpinum subspecies ecuadorense, endemic in Ecuador; C. parvum from Ecuador, Perú and Bolivia; and C. sasaimae, endemic in Colombia. Se describen e ilustran cuatro especies nuevas y una subespecie de Ceroxylon:, asf: C. amazonicum, C. echinulatum, y C. alpinum subespecie ecuadorense, endémicas de Ecuador; C. parvum, de Ecuador, Perú y Bolivia; and C. sasaimae, endémica de Colombia.